Strategies of Islamic Religious Education Teachers in Fostering Student Discipline at an Integrated Islamic Junior High School - Priyanto, Catur; Rohimah, Siti; Fatimah, Meti (Abjadia : International Journal of Education, 2025)
This study aims to describe the strategies and factors that influence the instilling of disciplined character in students at Mutiara Insan Islamic Middle School. The study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the instilling of discipline is implemented through four main strategies, namely: (1) religious habits in the form of morning prayers, recitation of the Koran, and roll call before studying to establish regular time; (2) the role model of teachers—especially Islamic Religious Education (PAI) teachers—and the implementation of rules accompanied by educational sanctions such as reading the Qur'an and reflection; (3) the development of a positive school culture that emphasizes the values of politeness, orderliness, and responsibility; and (4) collaboration with parents in supervising and fostering discipline at home. The success of this strategy is supported by four important factors, namely the leadership of the principal, the role of PAI teachers and other teachers as role models, an Islamic school culture integrated into learning activities, and support from parents and the environment. These findings indicate that the instilling of discipline at Mutiara Insan Islamic Middle School takes place in an integrative, sustainable manner and is able to become a model of Islamic character education that is relevant to the demands of the times.